Biogas Fermentation from Vegetable Waste and Horse Rumen Involving Effective Microorganism-4 (EM4) - Septiani, Mimin; Nuhardin, Irhamni; Muliawan, Arief (Politeknik Negeri Ujung Pandang, 2020)
A vegetable waste is an organic matter that contains cellulose which potential to be processed into biogas with anaerobic fermentation process. The aims of this research are to find out how long time to produce biogas from vegetable waste and horse Rumen by using EM4, what does the effect of the addition of EM4 to the biogas yield and the content of the produced gas. Vegetables waste and Rumen rasio 1:1 (500g:500g). Water Content of 500g. Addition variable of EM4 in each digester are 0 ml, 50 ml, 100 ml, 150 ml dan 200 ml. Fermentation process takes time about 3 to 15 days.Â This result shows that the average time of fermentation lasts up to 11 days. The addition of 150 ml EM4 generate the highest pressure, come to 322.801 Pa, capable of producing the highest biogas yield of 0.2679 % with CO2content of 5.15 %.